2020
DOI: 10.32725/jab.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

A study of the hepatoprotective effect of Plantago psyllium L. seed extract against Carbon tetrachloride induced hepatic injury in rats

Abstract: Background: The liver is the main metabolic organ involved in disposal and detoxification of various molecules. Plantago psyllium L. seed has been reported to exert positive effects in some pathological conditions. The current study aims to assess the hepatoprotective effect of Plantago psyllium L. seed extract against carbon tetrachloride-induced hepatotoxicity. Methods: Male albino Wistar rats were randomly divided into five groups of 10 rats each. Hepatotoxicity was induced by orally administered carbon tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…TNF-α is a marker for inflammatory illness and it is a pro-inflammatory cytokine that has a critical role in modifying many physiological events as well as inflammation. P. psyllium extract successfully reduced CCl4-induced inflammation and hence TNF-α expression, indicating its healing effect on liver cells via the controlling of cytokine expression and the underlying inflammatory process [ 104 ]. Aucubin (a type of iridoid glycoside) and Lantamajoside exhibited anti-inflammatory properties through the inhibitory effect of TPA (12-o-tetradecanoylphorbol-13-acetate) [ 105 ] and arachidonic acid metabolism, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-α is a marker for inflammatory illness and it is a pro-inflammatory cytokine that has a critical role in modifying many physiological events as well as inflammation. P. psyllium extract successfully reduced CCl4-induced inflammation and hence TNF-α expression, indicating its healing effect on liver cells via the controlling of cytokine expression and the underlying inflammatory process [ 104 ]. Aucubin (a type of iridoid glycoside) and Lantamajoside exhibited anti-inflammatory properties through the inhibitory effect of TPA (12-o-tetradecanoylphorbol-13-acetate) [ 105 ] and arachidonic acid metabolism, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that animals who received psyllium extract at variable doses showed no signs of toxicity, morbidity or changes in animal behaviour. Analysis of serum renal and hepatic biomarkers showed that a dose of up to 1000 mg/kg of the extract was safe without any side effects [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it may act as free radical scavenger and may be used to cure various disorders. Mekky and coworkers investigated antioxidant activity of psyllium seeds to protect against CCl 4 (free radical) induced-hepatotoxicity experimentally [23]. It also has enhanced endogenous antioxidant capability of hepatic tissue and inhibited lipid peroxidation.…”
Section: In Hepatic Diseasesmentioning
confidence: 99%
“…Other studies, in turn, would suggest potential applications of the hoary plantain that are waiting to be explored. For example, a hepatoprotective action was observed for the defatted aqueous methanolic extract obtained from the leaves of P. major (effect attributed to verbascoside) [ 70 ], P. ovata husk mucilage [ 78 ] and seed aqueous extract [ 79 ], P. asiatica seeds polysaccharide fraction [ 80 ], P. psyllium seeds ethanolic extract (for which the total phenolics and total flavonoids contents were determined as 16.17 mg gallic acid equivalents/g dried weight, respectively 1.9 mg rutin equivalents/g dried weight) [ 81 ] and P. albicans leaves aqueous extract (total phenolics content 592.75 mg gallic acid equivalents/g, total flavonoids content 116.7 mg catechin equivalents/g [ 82 ], in several hepatic damage models, Table 3 ). Considering the variety of extracts and fractions used, the results would suggest a hepatoprotective potential for the P. media, also.…”
Section: Plantago Media L Future Perspectivesmentioning
confidence: 99%